Desenvolvimento de um VANT do Tipo F450 para Vistoria de um Sistema de Proteção Contra Descargas Atmosféricas - Leonardo Marques de Freitas; Maycon Jean de Moura; Antonio Gomes Nunes; Alexsandro P. de Moura; Cláudio Gabriel V. Vale; Estefanie Rayane S. de Oliveira; Francisco Everardo Q. de Lima Filho; João Victor da Silva, (Anais do Encontro de Computação do Oeste Potiguar ECOP/UFERSA (ISSN 2526-7574), 2020)
UAVs (Unmanned Aerial Vehicles) are flying objects that have several applications, such as parcel delivery and object analysis at specific locations. Given its functionalities, this article aims to investigate an LPS (Lightning Protection System), normally located on top of buildings that are difficult for the operator to access, using a camera coupled to a UAV, built and configured in the laboratory, making it safer to analyze details of its structure and possible damage to be repaired. The procedure for carrying out this verification is shown through the description of the tests performed, which proved the efficiency of using UAV in capturing images.